Molecular characterization and antimicrobial profiling of Escherichia coli isolates from diarrheic calves - SHARMA, R K; TAKU, A K; MALIK, ANDLEEB; BHAT, M A; JAVED, RABYIA; BADROO, G A; KOUR, AMITOZ (The Indian Journal of Animal Sciences, 2018)
Diarrhea due to Escherichia coli is one of the major economic concerns of bovine industry in the first few weeks after birth. The present study was carried out for characterization of virulence traits of Escherichia coli associated with diarrhea in calves less than 3 months of age and their antimicrobial profiling. Escherichia coli isolates (700) were recovered in this study, which belonged to 25 different serogroups out of which O2 and O6 were most predominant. The isolates were screened for 7 virulence genes, viz. sta, stx1, stx2, lt, f5, f41 and eae. Out of 700 isolates, 65 (9.2%) carried virulence genes either alone (f5, eae, f41, sta, stx1 and stx2) or in different combinations (f41/sta, sta/lt, stx1/eae and f5/stx2). Based on the presence of virulence factors, these isolates were classified as Shiga-toxin producing E. coli (27), enterotoxigenic E. coli (20), enteropathogenic E. coli (15) and 3 were unclassified. These 65 isolates were resistant to commonly used antibacterial agents like amoxicillin, ceftriaxone, cephalexin, cloxacillin, enrofloxacin and gentamicin. Multidrug resistance was also observed in 84.6% of them.This study reveals that PCR based detection of E. coli virotypes can be used in diagnosis and epidemiological studies. Also increasing multidrug resistance for most of the commonly used antibiotics is a matter of concern.